Pemanfaatan Adsorben Karbon Cangkang Kemiri untuk Pemisah Lemak dan Minyak pada Air Limbah Rumah Makan - Nurhasannah, Sitti; Rosdiana, Rosdiana; Wibowo, Dwiprayogo (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2024)
This research study focus on Utilization of candlenut shell carbon adsorbent for separating oil and fat in restaurant wastewater. The problem in this study is the oil and fat in restaurant wastewater that has passed the domestic wastewater standard of 6.31 mg/L. The objectives of this research are to investigate the variation in mass of candllenut shell carbon adsorbent in separating oil and fat in restaurant wastewater and the effectiveness of canddlenut shell carbon adsorbent in separating oil and fat in restaurant wastewater. The method used with the use of a simple filtering device model with a direct flow of waste water by canddlenut shell carbon adsorbnet. The results of the study showed that at mass variations 25 grams had a high efficiency value with an efficiency of 17,43% and a kinetic value of the adsorption of left-handed carbon chewing k value of 1,2.10-3 min-1. The implications of this study are that the level of candllenut shell carbon effectiveness in separating oil and fat in the waste water of the food facilities is still less effective.